Navel healing in male and female Holstein calves over the first 14 days of life: A longitudinal cohort study - T.E. von Konigslow; T.F. Duffield; K. Beattie; C.B. Winder; D.L. Renaud; D.F. Kelton (Journal of Dairy Science, 2022)
ABSTRACT: The objectives of this study were (1) to describe navel healing in male and female neonatal Holstein calves over a 14-d observation period, and (2) to determine the associations of dam parity, calving factors, and calf factors with navel measurements and time to healing. A total of 68 Holstein calves (43 female and 25 male) were enrolled. Navel healing outcomes (cessation of navel discharge, navel cord remnant drying, navel cord remnant drop-off) and navel stump measurement outcomes (proximal diameter, distal diameter, length) were recorded every 24 ± 1 h for a 14-d observation period. Data were also collected for dam parity, calving factors (time of birth, calving ease), and calf factors (calf sex, calf vitality at birth, birth weight, average daily gain, serum total protein, and medical treatment or treatments). The mean time to navel cord remnant drying was 2 d, and all calves had dry navels by d 5. A total of 56% of calves retained their navel cord remnant beyond the end of the observation period, and calves began to shed their navel cord remnants as early as d 2. In addition, at least once during the observation period, 85% of calves had a proximal navel diameter measurement over a 13-mm threshold recently proposed to identify navel infections. For distal navel diameter measurements, 72% of calves had a diameter over the 13-mm threshold at least once during the observation period. No associations were identified between navel healing outcomes and dam, calving, and calf factors. Navel measurement outcomes were associated with calving and calf factors. Specifically, proximal navel stump diameter was associated with the day of observation (decreased from d 5 to 14), calf sex (smaller in female calves), time of birth (larger in calves born overnight or unobserved, compared with the morning), and birth weight (larger in birth weights >44.1 kg compared with <38.5 kg). Distal navel stump diameter was associated with calf sex, medical treatment, and day of observation; however, we observed an interaction between sex and day of observation (larger in male calves on d 3 to 7, d 9, and d 12, compared with female calves), and sex and medical treatment (larger in untreated male calves, no difference between treated male and female calves). Navel stump length was associated with time of birth (longer in calves born overnight or unobserved compared with any other time) and the interaction of birth weight and day of observation (longer in birth weights >44.1 kg compared with 38.6–41.5 kg on d 3, 8–10, and 13, and 41.6–44.0 kg on d 3, 5, 7–8, and 13). The wide range in time to navel cord remnant drying and drop-off suggest that these measures may not be adequate indicators of calf age on their own. More research on navel healing is required to improve our understanding of factors that influence navel measurements and time to healing, as well as how this information could be used in an objective assessment of navel health.